TLR4-mediated release of heparin-binding protein in human airways: a co-stimulatory role for IL-26 - Paulsson, Magnus; Cardenas, Eduardo I.; Che, Karlhans F.; Brundin, Bettina; Smith, Margaretha; Qvarfordt, Ingemar; Lindén, Anders (Frontiers in Immunology, 2023)
Background Bacterial infection causes accumulation of neutrophils that release antimicrobial proteins including heparin-binding protein (HBP). In human airways, this neutrophil accumulation can be re-capitulated via intrabronchial exposure to lipopolysaccharide (LPS), a Toll-like receptor 4 (TLR4) agonist, that also causes a local increase in the neutrophil-mobilizing cytokine IL-26. Although LPS is considered a weak stimulus for HBP release ex vivo, its effect on HBP release in human airways in vivo has not been characterized. Methods We determined whether intrabronchial exposure to LPS causes concomitant release of HBP and IL-26 in human airways, and whether IL-26 can enhance LPS-induced release of HBP in isolated human neutrophils. Results We found that the concentration of HBP was markedly increased in bronchoalveolar lavage (BAL) fluid 12, 24, and 48 hours after LPS exposure, and that it displayed a strong and positive correlation with that of IL-26. Moreover, the concentration of HBP in conditioned media from isolated neutrophils was enhanced only after co-stimulation with LPS and IL-26. Conclusions Taken together, our findings indicate that TLR4 stimulation causes concomitant release of HBP and IL-26 in human airways, and that IL-26 may constitute a required co-stimulant for HBP release in neutrophils, thus enabling the concerted action of HBP and IL-26 in local host defense.